DOP009 Comparative safety profile of vedolizumab and tumour necrosis factor–antagonist therapy for inflammatory bowel disease: a multicentre consortium propensity score-matched analysis. (16th January 2018) - Lukin, D; Weiss, A; Aniwan, S; Kadire, S; Tran, G; Rahal, M; Faleck, D; Winters, A; Chablaney, S; Meserve, J; Kochhar, G; Shashi, P; et al.
Abstract: Background: We compared the safety profile of vedolizumab (VDZ) to tumour necrosis factor (TNF)-antagonist therapy for Crohn's disease (CD) and ulcerative colitis (UC). Methods: Using a multicentre US-based consortium of CD and UC patients treated with VDZ or TNF-antagonist therapy, we performed propensity score matching (1:1) accounting for age, sex, prior disease-related hospitalisation within the previous year, disease phenotype (stricturing or penetrating complication history for CD, disease extent for UC), disease severity, prior bowel surgery for CD, steroid refractoriness or dependence, and prior TNF-antagonist failure. Rates of serious infections (SI) and serious adverse events (SAE) were compared using logistic regression analyses between matched VDZ- and TNF-antagonist–treated patients. SI were defined as requiring antibiotics or hospitalisation, or resulting in discontinuation or death. SAE were defined as SI or non-infectious adverse events resulting in discontinuation or death. Odds ratio (OR) and 95% confidence intervals (CIs) are reported for VDZ compared with TNF-antagonist therapy. Results: Of 1768 patients, 872 were included after matching ( n = 538 CD, n = 436 VDZ; 47% male, median age 35 years). VDZ-treated patients had numerically lower rates of SI (6.9% vs. 10.1%; OR 0.67, 95% CI 0.41–1.07) and significantly lower rates of SAE (7.1% vs. 13.1%; OR 0.51, 95% CI 0.32–0.81). SI and SAE were reported in 6.8% and 9.1% of patients on biologic monotherapy, 8% and 9.3% on biologic therapy in combination with either steroids or an immunomodulator, and 12.7% and 14% on biologic therapy in combination with both steroids and an immunomodulator. Among matched patients on biologic monotherapy ( n = 247; n = 142 VDZ), VDZ-treated patients had numerically lower rates of SI (4.1% vs. 10.1%; OR 0.37, 95% CI 0.13–1.02) and significantly lower rates of SAE (4.7% vs. 14.5%; OR 0.29, 95% CI 0.12–0.73). Among matched patients on biologic therapy in combination with both steroids and an immunomodulator ( n = 137; n = 69 VDZ), rates of SI (11.5% vs. 13.9%, OR 0.81, 95% CI 0.31–2.07) and SAE (14% vs. 14%, OR 0.66, 95% CI 0.27–1.65) were similar between VDZ- and TNF-antagonist–treated patients. Conclusions: In clinical practice, rates of SI and SAE were lower with VDZ than with TNF-antagonist therapy. Concomitant immunosuppressive use was associated with an increased risk for both SI and SAE, and rates were similar between VDZ and TNF-antagonist therapy when using concomitant immunosuppressive therapy. Further studies are needed to understand the importance of concomitant immunosuppressive therapy for VDZ as this has significant implications on its safety profile.